Efeitos das radiações ionizantes de raios-X no SOI nMOSFET com geometria de porta octogonal - Fino, L. N. S. (2017)
This work explores the analog and digital applications of unconventional layouts for Metal-Oxide-Semiconductor Field Effect Transistors (MOSFETs) manufactured in Silicon-On-Insulator Technology (SOI) under a X-ray ionizing radiation effects. On this way, an experimental comparative study of the effects of Total Ionizing Doses (TID) on the main electrical parameters and merit figures of the SOI nMOSFETs with octagonal (Octagonal SOI nMOSFET, OSM), conventional rectangular (Conventional SOI nMOSFET, CSM) and (Diamond SOI nMOSFET, DSM). All SOI nMOSFETs were designed by the Advanced MOSFETs research group at FEI University Center and manufactured using 0.5 µm SOI technology from the Catholic University of Louvain. OSM, due to its octagonal gate geometry, produces a higher longitudinal electric field to the equivalent CSM due to the Longitudinal Corner Effects (LCE) and due to the effect of the PArallel Conection of MOSFETs with Different Channel Lenght Effect (PAMDLE). The OSM is also able to minimize an influence of parasitic transistors from the bird´s beak regions in X-ray ionizing radiation environments, since the longitudinal electric field lines are curved in these regions. This effect was titled Deactivation of the Parasitic MOSFETs in the Bird s Beak Regions Effect (DEPAMBBRE) .The configuration of the OSMs that obtained the best results after the effects of the TID in all bias conditions of the MOSFETs during the X-ray procedure, was the device with a cut factor c equal 25% and angle "a" equal 53, 1°. Considering the different bias of the SOI nMOSFETs during the X-ray irradiation procedure, in the passive or floating condition, the OSM obtained higher or-similar results to the CSM equivalent in 92% of the parameters analyzed. Considering the on state bias (condition that potentiates the vertical electric field), OSM obtained higher or similar results in 83% of the analyzed parameters than the equivalent CSM. Furthermore, adopting the off-state bias (condition that maximizes the horizontal electric field), OSM obtained higher or similar results in 75% of the analyzed parameters than the equivalent CSM. These results suggest the application of OSM mainly for applications of analog Complementary Metal-Oxide-Semiconductor (CMOS) integrated circuits (ICs). The tolerance of the OSM considering each electrical parameters in function of TID when compared with equivalent CSM decreases as the longitudinal electric field of the OSM is intensified as a function of the bias condition adopted during x-ray procedures. The worst case is the off-state condition. This is justified due to LCE and PAMDLE effects found in the OSM structure. Even so, the OSM continues to be more tolerant to the TID effects due to x-ray radiation than the equivalent CSM considering all bias conditions.